2009
DOI: 10.1029/2008ja013729
|View full text |Cite
|
Sign up to set email alerts
|

THEMIS observations of the near‐Earth plasma sheet during a substorm

Abstract: [1] We present observations of a substorm on 13 March 2008 by Time History of Events and Macroscale Interactions during Substorms (THEMIS) spacecraft in the near-Earth tail during the plasma sheet expansion evidenced by increase in the plasma density and temperature. The main features of the event are as follows: (1) Cross-tail current reduction or current disruption (CD) was observed in the near-Earth tail at X $ À8.0 R E and Y $ 2.0 R E , marked by a sharp drop of jB x j and accompanied by sharp increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
(56 reference statements)
3
18
0
Order By: Relevance
“…Mauk, 1986;Zhou et al, 2010), and both the ion density and β could increase several times after the dipolarization process (e.g. Zhang et al, 2007;Tang et al, 2009), which indicate that the R value of plasma should increase. There are also many observations that show that the dipolarization process, coupled with electron acceleration and wave particle interactions, can account for electron heating (see, for example, Ashour-Abdalla et al, 2009;Fu et al, 2011).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Mauk, 1986;Zhou et al, 2010), and both the ion density and β could increase several times after the dipolarization process (e.g. Zhang et al, 2007;Tang et al, 2009), which indicate that the R value of plasma should increase. There are also many observations that show that the dipolarization process, coupled with electron acceleration and wave particle interactions, can account for electron heating (see, for example, Ashour-Abdalla et al, 2009;Fu et al, 2011).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…After the substorm injections, the electron fluxes had very significant increases (Figures 3b and 3c). The rest of electron energy spectra (marked by the gray bar in Figures 4a and 4b) indicated that RBSP-A was located in the near-Earth plasma sheet [e.g., Lui, 1996;Tang et al, 2009]. For 1.8 MeV electrons, the substorm injections yielded P r = j 3 /j 2 = 3.4 and P e = j 3 /j 1 = 2.1 (P r and P e are the recovery and enhancement coefficients of 1.8 MeV electron fluxes, respectively).…”
Section: Themis-a and Geosynchronous Orbit Satellite Observationsmentioning
confidence: 99%
“…Usually, the intensive electric fields can propagate inward and produce dipolarization and dispersionless injections in the outer radiation belt [e.g., Li et al, 1998;Sarris et al, 2002]. After~03:12 UT (as indicated by the second vertical dashed line), the intensive electron fluxes were also observed (Figure 2d), which indicated that THEMIS-A was in an expanding plasma sheet [e.g., Lui, 1996;Tang et al, 2009]. After~03:12 UT (as indicated by the second vertical dashed line), the intensive electron fluxes were also observed (Figure 2d), which indicated that THEMIS-A was in an expanding plasma sheet [e.g., Lui, 1996;Tang et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…During the tailward‐moving dipolarization interval, the plasma temperature T i and pressures ( P t and P p ) at P4 and P5 increased. These changes are the typical signatures in the near‐Earth tail during the dipolarization interval [ Tang et al ., ]. Meanwhile, the magnetic field configuration in the near‐Earth tail became more dipolar (see Figures b and b).…”
Section: Observationsmentioning
confidence: 99%
“…Understanding the intrinsic nature of the dipolarization phenomenon is crucial for clarifying the substorm onset question. One possible explanation for the dipolarization is that the ballooning [ Roux et al ., ] or cross‐field current instabilities [ Lui et al ., ; Tang et al ., ] produce the disruption of cross‐tail current in the near‐Earth tail. Another explanation is that dipolarizations are caused by the pileup of the magnetic flux at the inner edge of the plasma sheet where the earthward flows encounter a high‐pressure region and are braked [ Shiokawa et al ., ; Baumjohann , ; Tang et al ., ].…”
Section: Introductionmentioning
confidence: 99%